The Appropriate Particle Size of Dazomet Can Ensure the Soil Fumigation Effect from the Source - Daqi Zhang; Lirui Ren; Wenjing Li; Qing Wang; Shenyan Liu; Xi Jin; Wensheng Fang; Dongdong Yan; Yuan Li; Qiuxia Wang; Qingli Han; Lin He; et al. (Agriculture, 2022)
Dazomet (DZ) is a soil fumigant that has been used for decades at many countries, however it was reported to have caused phytotoxicity and reduced crop yield in many countries. In this experiment, in order to clarify whether the diameter of DZ is related to phytotoxicity, this research investigated the degradation rate of DZ with different diameter ranges under three soil types held at 15, 20 or 30% soil water content at 4, 15, 25 or 37 °C, and monitored concentrations of methyl isothiocyanate (MITC) produced when Shunyi soil was fumigated with DZ using the different particle sizes ranges. When the soil water content and temperature increased, the degradation rate of DZ with different particle sizes accelerated. However, the degradation rate of DZ with large particle sizes was still lower than small particle sizes. NO3−-N, available phosphorus (AP), available potassium (AK), pH and silt content in the soil were all significantly positively correlated with <100 μm DZ, and significantly negatively correlated with 300–400 μm and >400 μm DZ. However, organic matter (OM) and sand content produced the opposite result. The maximum concentration of MITC produced by 100–300 μm of DZ in 25 °C Shunyi soil at 30% water content were 102.2 mg/kg at 24 h. DZ produced peaks significantly higher and earlier at 30% than at 20% soil water content. We recommend selecting DZ manufactured with particle in the range of 100 to 300 μm, fumigating at about 25 °C and ensuring that about 30% soil water content is present in the soil immediately after fumigation.